Compound, organic thin film light emitting element, display device and lighting device
By using the compound represented by the general formula (1), the specific polycyclic aromatic hydrocarbon and linking group structure are used to improve the luminescence efficiency and durability life of the organic thin film luminescence element, and the problem of insufficient luminescence efficiency and durability life in the prior art is solved.
Patent Information
- Application Number
- CN202080082975.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2020-10-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-10-28
AI Technical Summary
The existing organic thin film luminescent elements have shortcomings in terms of luminescence efficiency and durability life, and it is difficult to achieve efficient luminescence and long life at the same time.
The compound represented by the general formula (1) contains a specific structure of polycyclic aromatic hydrocarbons and linking groups. By extending molecules to improve intermolecular interactions, promote charge transportability and membrane stability, thereby reducing driving voltage and improving luminescence efficiency.
It achieves high luminous efficiency and excellent durability life, can drive at low voltage and improve the performance of the luminous emitting element.
Smart Images

Figure CN114746402B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a compound having a specific structure, an organic thin film light emitting element, a display device and a lighting device using the compound. Background Art
[0002] In recent years, organic thin film light emitting elements have been steadily being put into practical use in displays for televisions and smartphones. However, there are still many technical issues in existing organic thin film light emitting elements. Among them, achieving high-efficiency light emission and extending the life of organic thin film light emitting elements have become major issues.
[0003] As compounds for solving these problems, fluoranthene derivatives having a fluoranthene skeleton and an aromatic heterocyclic group containing electron-accepting nitrogen (for example, refer to Patent Document 1), compounds having a pyrene skeleton and an aryl or heteroaryl group (for example, refer to Patent Document 2, Non-Patent Document 1), compounds having a cyano group and a heteroaryl group (for example, refer to Patent Document 3), compounds having a triphenylene skeleton and an aromatic heterocyclic ring containing electron-accepting nitrogen (for example, refer to Patent Document 4), etc. have been developed so far.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2015 / 182547
[0007] Patent Document 2: International Publication No. 2012 / 173073
[0008] Patent Document 3: Japanese Patent Publication No. 2018-532688
[0009] Patent Document 4: International Publication No. 2016 / 060322
[0010] Non-patent literature
[0011] Non-patent document 1: Sensors, (Switzerland), May 13, 2009, 9(5), p.3604-3626 Summary of the invention
[0012] Problems to be solved by the invention
[0013] According to Patent Documents 1 to 2 or Non-Patent Document 1, a compound having a specific structure in which a nitrogen-containing aromatic heterocycle is linked to fluoranthene or pyrene can be used to obtain an organic thin film light-emitting element that has improved luminous efficiency, can be driven at low voltage, and has excellent durability. In addition, Patent Documents 3 to 4 disclose that a compound having a specific structure in which a cyano or triphenylene skeleton is linked to a nitrogen-containing aromatic heterocycle can be used to obtain an organic thin film light-emitting element with excellent durability. However, in recent years, the luminous efficiency and durability required of organic thin film light-emitting elements have been increasingly improved, and a technology that allows high luminous efficiency and long life to coexist is required.
[0014] The present invention has been made in view of the above-mentioned problems in the prior art, and an object of the present invention is to provide an organic thin film light emitting element having excellent luminous efficiency and long life.
[0015] Technical means of solving problems
[0016] The present invention is a compound represented by the following general formula (1).
[0017] [Chemistry 1]
[0018]
[0019] In the general formula (1), X 1 ~X 3 Any one of them is a nitrogen atom, and the others are methine atoms. 1 is a substituted or unsubstituted biphenylene, terphenylene, naphthylene, quaterphenylene, dimethylfluorenylene, diphenylfluorenylene or spirobifluorenylene. Wherein, the substituents of these groups when substituted are alkyl or alkoxy. A is a phenanthryl, pyrenyl, dimethylfluorenyl, diphenylfluorenyl or spirobifluorenyl.
[0020] Effects of the Invention
[0021] According to the present invention, an organic thin film light emitting element having excellent luminous efficiency and durable life can be provided. DETAILED DESCRIPTION
[0022] Preferred embodiments of the compound, organic thin film light emitting device, display device and lighting device of the present invention are described in detail below. However, the present invention is not limited to the following embodiments, and can be implemented with various modifications according to the purpose or application.
[0023] (Compound represented by general formula (1))
[0024] The compound represented by the general formula (1) which is one embodiment of the present invention is the compound shown below.
[0025] [Chemistry 2]
[0026]
[0027] In the general formula (1), X 1 ~X 3 Any one of them is a nitrogen atom, and the others are methine atoms. 1 is a substituted or unsubstituted biphenylene, terphenylene, naphthylene, quaterphenylene, dimethylfluorenylene, diphenylfluorenylene or spirobifluorenylene. Wherein, the substituents of these groups when substituted are alkyl or alkoxy. A is a phenanthryl, pyrenyl, dimethylfluorenyl, diphenylfluorenyl or spirobifluorenyl.
[0028] In the case of "substituted or unsubstituted", "unsubstituted" means that hydrogen atoms are bonded, and "substituted" means that at least a part of the hydrogen atoms are substituted. In the compounds or partial structures described below, the same applies to the case of "substituted or unsubstituted".
[0029] The so-called alkyl group refers to a saturated aliphatic hydrocarbon group such as a methyl group, an ethyl group, a n-propyl group, an isopropyl group, a n-butyl group, a sec-butyl group, a tert-butyl group, etc., which may or may not have a substituent. The carbon number of the alkyl group is not particularly limited, but is generally in the range of 1 to 20, more preferably 1 to 8, from the perspective of ease of acquisition or cost.
[0030] The so-called alkoxy group refers to a group formed by bonding an alkyl group such as a methoxy group, an ethoxy group, a n-propoxy group, an isopropoxy group, an n-butoxy group, a sec-butoxy group, a tert-butoxy group, and an oxygen group, and may or may not have a substituent. The number of carbon atoms in the alkoxy group is not particularly limited, but is generally in the range of 1 to 20, more preferably 1 to 8, from the perspective of ease of acquisition or cost.
[0031] As conventional compounds containing nitrogen-containing aromatic heterocycles and polycyclic aromatic hydrocarbons, for example, Patent Documents 1 to 4 and Non-Patent Document 1 show Compound X, Compound Y, Compound Z, Compound V, and Compound W represented by the following formulae.
[0032] [Chemistry 3]
[0033]
[0034] However, even when these compounds are used as light-emitting element materials in electron injection layers, electron transport layers or charge generation layers, sufficient performance has not yet been achieved for the characteristics required in recent years, and there is a demand for the creation of compounds that can further improve performance in terms of luminous efficiency and long life.
[0035] For example, the driving voltage of the compound with fluoranthene group such as compound X is high, and there are still problems in terms of luminous efficiency and durable life. In addition, the compound such as compound Y that connects nitrogen-containing aromatic heterocycles and polycyclic aromatic hydrocarbons through phenylene groups has a small effect of improving the intermolecular interaction brought by the linking group, so it is difficult to fully reduce the driving voltage, and there are problems in terms of luminous efficiency and durable life. In addition, the compound with cyano group and nitrogen-containing aromatic heterocycle such as compound Z has a cyano group and the lowest unoccupied molecular orbital (Lowest Unoccupied Molecular Orbital, LUMO) energy level becomes too deep, so the driving voltage becomes high, and there are problems in terms of luminous efficiency and durable life. Compounds with multiple pyrene groups such as compound V or compounds with triphenylenyl group such as compound W are easy to crystallize in the element due to their high crystallinity, and there are problems in terms of durable life and driving stability.
[0036] In their research for improvement, the present inventors have focused on the effects of specific polycyclic aromatic hydrocarbons and these linking groups. 1 A linking group having a molecular weight larger than that of the phenylene group is introduced. By extending the molecule, the interaction between the molecules is improved, and it is easy to orient horizontally in the vapor-deposited film. Due to these effects, the charge transport property can be further increased, the driving voltage can be reduced, and the luminous efficiency can be improved. In addition, by increasing the interaction between the molecules, the glass transition temperature can be increased, and the durable life can be improved. Furthermore, as A, a phenanthryl, pyrenyl, dimethylfluorenyl, diphenylfluorenyl or spirobifluorenyl having high planarity and large molecular overlap is selected to have high charge transport property, so it can be driven at low voltage and improve the luminous efficiency.
[0037] The compound represented by the general formula (1) has a large electron transport property. In addition, since it is a flexible structure containing multiple pyridine groups, it has a large coordination property to metal atoms. Therefore, when the compound represented by the general formula (1) is used in the organic layer in the light-emitting element, a stable layer can be formed. In particular, when the organic layer is an electron transport layer, an electron injection layer or a charge generation layer, these layers show more stable and excellent performance.
[0038] In the general formula (1), X 1 ~X 3 Any one of X is a nitrogen atom, and the others are methine atoms. From the viewpoint of improving the coordination to the metal atom and forming a more stable layer, X 3 Nitrogen atoms are preferred. By forming a layer in which coordination is performed more stably, low voltage driving is possible, and the durability life is further improved.
[0039] In the general formula (1), L 1is a substituted or unsubstituted biphenylene, terphenylene, naphthylene, quaterphenylene, dimethylfluorenylene, diphenylfluorenylene or spirobiflourenylene. 1 When L is one of these groups, the interaction between molecules is enhanced as described above, and the charge transport property or the film stability can be further improved. 1 Preferably, it is substituted or unsubstituted biphenylene, terphenylene, naphthylene, more preferably substituted or unsubstituted biphenylene. By selecting these groups, the charge transport property is improved, thereby low voltage driving can be achieved, and the luminous efficiency is further improved. In addition, by selecting these groups, the film stability is improved, thereby further improving the durable life.
[0040] L 1 When substituted, the substituent is an alkyl group or an alkoxy group, which is preferred because it can improve the stability of the compound without reducing the charge transport property of the compound.
[0041] In the general formula (1), A is a phenanthryl group, a pyrenyl group, a dimethylfluorenyl group, a diphenylfluorenyl group or a spirobifluorenyl group. From the viewpoint of further improving the luminous efficiency and the durable life, A is preferably a pyrenyl group.
[0042] Examples of the compound represented by the general formula (1) include the following compounds: The following are illustrative only, and any compound other than the compounds explicitly described herein can also be preferably used as long as it is a compound represented by the general formula (1).
[0043] [Chemistry 4]
[0044]
[0045] [Chemistry 5]
[0046]
[0047] [Chemistry 6]
[0048]
[0049] [Chemistry 7]
[0050]
[0051] [Chemistry 8]
[0052]
[0053] [Chemistry 9]
[0054]
[0055] [Chemistry 10]
[0056]
[0057] [Chemistry 11]
[0058]
[0059] [Chemistry 12]
[0060]
[0061] [Chemistry 13]
[0062]
[0063] [Chemistry 14]
[0064]
[0065] The compound represented by the general formula (1) can be synthesized by a known synthesis method. Examples of the synthesis method include a coupling reaction of a halogenated aryl derivative and an arylboronic acid derivative using palladium, but the present invention is not limited thereto.
[0066] The compound represented by the general formula (1) can be preferably used as a light-emitting element material. Here, the light-emitting element material in the present invention refers to the material used in any layer of the light-emitting element, as described later, in addition to the materials used in the hole injection layer, the hole transport layer, the light-emitting layer and / or the electron transport layer, it also includes the material used in the protective film layer (covering layer) of the electrode. By using the compound represented by the general formula (1) in the present invention in any layer of the light-emitting element, high luminous efficiency can be obtained, and a light-emitting element with excellent durability can be obtained.
[0067] (Organic thin film light emitting element)
[0068] Next, an embodiment of an organic thin film light emitting device is described in detail. The organic thin film light emitting device has an anode and a cathode, and an organic layer interposed between the anode and the cathode, and the organic layer emits light by electrical energy.
[0069] In addition to the structure containing only the light-emitting layer, the layer structure between the anode and the cathode in this organic thin film light-emitting element can include the following stacked structures: 1) light-emitting layer / electron transport layer, 2) hole transport layer / light-emitting layer, 3) hole transport layer / light-emitting layer / electron transport layer, 4) hole injection layer / hole transport layer / light-emitting layer / electron transport layer, 5) hole transport layer / light-emitting layer / electron transport layer / electron injection layer, 6) hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer, 7) hole injection layer / hole transport layer / light-emitting layer / hole blocking layer / electron transport layer / electron injection layer, etc.
[0070] Furthermore, it can also be a tandem type in which a plurality of the stacked structures are stacked via an intermediate layer. The intermediate layer is also generally referred to as an intermediate electrode, an intermediate conductive layer, a charge generation layer, an electron extraction layer, a connecting layer, and an intermediate insulating layer, and a known material structure can be used. As a specific example of the tandem type, for example, there can be listed: 8) hole transport layer / luminescent layer / electron transport layer / charge generation layer / hole transport layer / luminescent layer / electron transport layer, 9) hole injection layer / hole transport layer / luminescent layer / electron transport layer / electron injection layer / charge generation layer / hole injection layer / hole transport layer / luminescent layer / electron transport layer / electron injection layer, etc., a stacked structure including a charge generation layer as an intermediate layer between the anode and the cathode.
[0071] In addition, each of the layers may be a single layer or a multilayer, and may be doped. Furthermore, the organic thin film light emitting element may include a layer using a covering material, and the covering material improves the light emission efficiency due to the optical interference effect.
[0072] The compound represented by the general formula (1) can be used in any of the layers in the light-emitting element, and can be particularly preferably used in the electron transport layer, the charge generation layer or the electron injection layer. The organic thin film light-emitting element of the present invention is preferably a structure having at least an electron transport layer between the anode and the cathode and containing the compound represented by the general formula (1) in the electron transport layer, a structure having at least a charge generation layer and a light-emitting layer between the anode and the cathode and containing the compound represented by the general formula (1) in the charge generation layer, or a structure having at least an electron injection layer and a light-emitting layer between the anode and the cathode and containing the compound represented by the general formula (1) in the electron injection layer.
[0073] In the light emitting element of the embodiment of the present invention, the anode and cathode have the function of supplying a current sufficient to make the element emit light, and in order to output light, it is desirable that at least one of them is transparent or semi-transparent. The anode formed on the substrate is usually a transparent electrode.
[0074] (Substrate)
[0075] In order to maintain the mechanical strength of the light-emitting element, it is preferred to form the light-emitting element on a substrate. As the substrate, glass substrates such as soda glass or alkali-free glass, or plastic substrates, etc. can be listed. The thickness of the glass substrate only needs to be thick enough to maintain the mechanical strength, and it is sufficient as long as it is 0.5 mm or more. Regarding the material of the glass, it is preferred that there are few ions dissolved from the glass, and alkali-free glass is preferred. In addition, soda-lime glass with a barrier coat of SiO2 or the like is also commercially available, and the glass can also be used.
[0076] (anode)
[0077] The material used in the anode is preferably capable of injecting holes efficiently into the organic layer. In addition, in order to output light, it is preferably transparent or translucent. As the material used in the anode, for example, conductive metal oxides such as zinc oxide, tin oxide, indium oxide, indium tin oxide (Indium Tin Oxide, ITO), indium zinc oxide (Indium Zinc Oxide, IZO) can be listed; or metals such as gold, silver, chromium; inorganic conductive substances such as copper iodide and copper sulfide; conductive polymers such as polythiophene, polypyrrole, polyaniline, etc. Among these, ITO glass or NESA glass is preferred. These electrode materials can be used alone, or multiple materials can be stacked or mixed for use. Regarding the resistance of the transparent electrode, as long as a current sufficient to make the element emit light can be supplied, from the perspective of the power consumption of the element, it is preferably a low resistance. For example, if it is an ITO substrate below 300Ω / Υ, it functions as an element electrode, but currently a substrate of about 10Ω / Υ can also be supplied, so it is preferred to use a substrate with a low resistance of less than 20Ω / Υ. The thickness of ITO can be arbitrarily selected according to the resistance value, but is usually used between 45 nm and 300 nm in many cases.
[0078] (cathode)
[0079] The material used in the cathode is not particularly limited as long as it is a substance that can efficiently inject electrons into the light-emitting layer. As the material used in the cathode, for example, metals such as platinum, gold, silver, copper, iron, tin, aluminum, and indium, or alloys or multilayer stacks of these metals with low work function metals such as lithium, sodium, potassium, calcium, and magnesium, etc. Among them, in terms of resistance value or ease of film formation, film stability, luminous efficiency, etc., it is preferably aluminum, silver, and magnesium as the main components, and in terms of easy electron injection into the electron transport layer and the electron injection layer, it is more preferably magnesium and silver.
[0080] (Protective layer)
[0081] In order to protect the cathode, it is preferred to stack a protective layer (covering layer) on the cathode. The material constituting the protective layer is not particularly limited, and examples thereof include: metals such as platinum, gold, silver, copper, iron, tin, aluminum and indium, alloys of these metals, inorganic substances such as silicon dioxide, titanium oxide and silicon nitride, organic polymer compounds such as polyvinyl alcohol, polyvinyl chloride, hydrocarbon polymer compounds, etc. In addition, the compound represented by general formula (1) can also be used as a protective layer. Among them, in the case where the light-emitting element is an element structure that outputs light from the cathode side (top emission structure), the material used for the protective layer is preferably light-transmitting in the visible light region.
[0082] (Hole Injection Layer)
[0083] The hole injection layer is a layer inserted between the anode and the hole transport layer. The hole injection layer may be a single layer or a plurality of layers may be stacked, either of which is acceptable. If there is a hole injection layer between the hole transport layer and the anode, the device is driven at a lower voltage, and the durability life is also improved. In addition, the carrier balance of the device is improved, and the luminous efficiency is also improved, so it is preferred.
[0084] The material used for the hole injection layer is not particularly limited, for example, 4,4'-bis(N-(3-methylphenyl)-N-phenylamino)biphenyl (N,N,N',N'-tetraphenyl-1,1'-biphenyl-4,4'-diamine (N,N,N',N'-Tetraphenyl-1,1'-biphenyl-4,4'-diamine, TPD)), 4,4'-bis(N-(1-naphthyl)-N-phenylamino)biphenyl (N,N'-diphenyl-N,N'-(1-naphthyl)-1, 1'-biphenyl-4,4'-diamine (N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, NPD), 4,4'-bis(N,N-bis(4-biphenyl)amino)biphenyl (tetrabiphenylyldiaminobiphenyl, TBDB), bis(N,N'-diphenyl-4-aminophenyl)-N,N-diphenyl-4,4'-diamino-1,1'-biphenyl (TPD232) and other benzidine derivatives, 4,4',4"-tris(3-methylphenyl(phenyl)amino)triphenylamine (m-MTDATA), 4,4',4"-tris(1-naphthyl(phenyl)amino)triphenylamine e, 1-TNATA) and other material groups called starburst arylamines, triarylamine derivatives, bis(N-arylcarbazole), bis(N-alkylcarbazole) and other biscarbazole derivatives, pyrazoline derivatives, distyrene compounds, hydrazone compounds, benzofuran derivatives, thiophene derivatives, oxadiazole derivatives, phthalocyanine derivatives, porphyrin derivatives and other heterocyclic compounds, polycarbonate or styrene derivatives, polythiophene, polyaniline, polyfluorene, polyvinylcarbazole, polysilane and other polymer materials having the above monomers in the side chain, etc. From the viewpoint of smoothly injecting and transporting holes from the anode to the hole transport layer, benzidine derivatives and starburst arylamine material groups can be more preferably used.
[0085] These materials can be used alone or in combination of two or more materials. In addition, multiple materials can be stacked to form a hole injection layer. Furthermore, if the hole injection layer is composed of an acceptor compound alone, or if the hole injection material as described above is doped with an acceptor compound for use, the effect can be more significantly obtained, so it is more preferred. The so-called acceptor compound, when used as a monolayer film, refers to the material constituting the contacted hole transport layer; when used as a doped film, it refers to the material constituting the hole injection layer and the material forming the charge transfer complex. If such a material is used, the conductivity of the hole injection layer is improved, which is more helpful to reduce the driving voltage of the element, and can further improve the luminous efficiency or durability.
[0086] As acceptor compounds, for example, metal chlorides such as iron (III) chloride, aluminum chloride, gallium chloride, indium chloride, and antimony chloride, metal oxides such as molybdenum oxide, vanadium oxide, tungsten oxide, and ruthenium oxide, charge transfer complexes such as tris (4-bromophenyl) ammonium hexachloroantimonate (TBPAH), organic compounds having nitro, cyano, halogen or trifluoromethyl in the molecule, quinone compounds, acid anhydride compounds, fullerenes, etc. Among these, metal oxides or cyano-containing compounds are easy to handle and easy to evaporate, so the effect can be easily obtained, so they are preferred. In either case where the hole injection layer is composed of an acceptor compound alone or in the case where an acceptor compound is doped in the hole injection layer, the hole injection layer may be a single layer or a plurality of layers may be stacked and constituted.
[0087] (Hole Transport Layer)
[0088] The hole transport layer is a layer that transports holes injected from the anode to the light-emitting layer. The hole transport layer may be a single layer or a plurality of layers stacked together, and any of them may be used.
[0089] As the material used in the hole transport layer, the materials exemplified as the material used in the hole injection layer can be mentioned. From the viewpoint of smoothly injecting and transporting holes to the light-emitting layer, triarylamine derivatives and benzidine derivatives are more preferred.
[0090] (Luminous layer)
[0091] The light-emitting layer may be a single layer or a multilayer, and is formed by a light-emitting material (a main material and a dopant material), which may be a mixture of a main material and a dopant material, a single main material, or a mixture of two main materials and a dopant material, either of which may be used. That is, with respect to the light-emitting element in the embodiment of the present invention, in each light-emitting layer, only the main material or the dopant material may emit light, or both the main material and the dopant material may emit light. From the perspective of efficiently utilizing electrical energy and obtaining light with high color purity, the light-emitting layer preferably comprises a mixture of a main material and a dopant material. In addition, the main material and the dopant material may be one or a combination of multiple materials, either of which may be used. The dopant material may be contained in the entire main material or in a part of the main material, either of which may be used. The dopant material may be stacked or dispersed, either of which may be used. The dopant material may control the luminescent color. From the perspective of suppressing concentration quenching, the amount of the dopant material is preferably less than 30% by weight, and more preferably less than 20% by weight, relative to the main material. Regarding the doping method, it can be formed by co-evaporation with the host material, but it can also be mixed with the host material in advance and then evaporated at the same time.
[0092] Examples of the light-emitting material include condensed ring derivatives of anthracene or pyrene known as light-emitting bodies, metal chelated oxinoid compounds such as tris(8-hydroxyquinoline)aluminum, distyryl derivatives such as distyryl anthracene derivatives or distyryl benzene derivatives, tetraphenylbutadiene derivatives, indene derivatives, coumarin derivatives, oxadiazole derivatives, pyrrolopyridine derivatives, perinone derivatives, cyclopentadiene derivatives, oxadiazole derivatives, thiadiazolopyridine derivatives, dibenzofuran derivatives, carbazole derivatives, indolecarbazole derivatives, or polymers such as polyphenylene vinylene derivatives, polyparaphenylene derivatives, and polythiophene derivatives.
[0093] The host material contained in the luminescent material is not limited to only one compound, and multiple compounds may be mixed or more than one other host material may be mixed. In addition, it may be used in layers. The host material is not particularly limited, and examples thereof include naphthalene, anthracene, phenanthrene, pyrene, Compounds having condensed aromatic rings such as tetracene, triphenylene, perylene, fluoranthene, fluorene, and indene, or their derivatives; aromatic amine derivatives such as N,N'-dinaphthyl-N,N'-diphenyl-4,4'-diphenyl-1,1'-diamine; metal chelated oxine compounds such as tri(8-hydroxyquinoline)aluminum(III); distyryl derivatives such as distyrylbenzene derivatives; tetraphenylbutadiene derivatives; indene derivatives; coumarin derivatives; oxadiazole derivatives; pyrrolopyridine derivatives; perinone derivatives; cyclopentadiene derivatives; pyrrolopyrrole derivatives; thiadiazolopyridine derivatives; dibenzofuran derivatives; carbazole derivatives; indolocarbazole derivatives; triazine derivatives; or polymers such as polyphenylene vinylene derivatives, polyparaphenylene derivatives, polyfluorene derivatives, polyvinylcarbazole derivatives, and polythiophene derivatives. Among them, as a host material used when the light-emitting layer emits triplet light (phosphorescence), metal chelated oxine compounds, dibenzofuran derivatives, dibenzothiophene derivatives, carbazole derivatives, indolocarbazole derivatives, triazine derivatives, triphenylene derivatives, etc. can be preferably used.
[0094] Examples of the dopant material contained in the light-emitting material include compounds having an aromatic ring such as naphthalene, anthracene, phenanthrene, pyrene, fluoranthene, triphenylene, perylene, fluorene, indene, or derivatives thereof (e.g., 2-(benzothiazol-2-yl)-9,10-diphenylanthracene or 5,6,11,12-tetraphenylnaphthacene), furan, pyrrole, thiophene, silole, 9-silicon fluorene, 9,9'-spirodisilicon fluorene, benzothiophene, benzofuran, indole, dibenzothiophene, dibenzofuran, imidazopyridine, phenanthroline, pyrazine, naphthyridine, quinoxaline, pyrrolopyridine, thioxanthene, or derivatives thereof, distyrylbenzene derivatives, 4,4'-bis(2-(4-diphenylaminophenyl)vinyl)biphenyl, 4,4'-bis(2-(4-diphenylaminophenyl)vinyl)biphenyl, and the like. Aminostyryl derivatives such as 4'-bis(N-(stilbene-4-yl)-N-phenylamino)stilbene, aromatic acetylene derivatives, tetraphenylbutadiene derivatives, stilbene derivatives, aldazine derivatives, pyrromethene derivatives, diketopyrrolo[3,4-c]pyrrole derivatives, coumarin derivatives such as 2,3,5,6-1H,4H-tetrahydro-9-(2'-benzothiazolyl)quinolizino[9,9a,1-gh]coumarin, azole derivatives such as imidazole, thiazole, thiadiazole, carbazole, oxazole, oxadiazole, triazole, and metal complexes thereof, aromatic amine derivatives such as N,N'-diphenyl-N,N'-di(3-methylphenyl)-4,4'-diphenyl-1,1'-diamine, etc. Among them, a dopant containing a diamine skeleton or a dopant containing a fluoranthene skeleton is preferred because the luminous efficiency can be further improved.
[0095] In addition, the dopant used when the light-emitting layer performs triplet light emission (phosphorescent light emission) is preferably an organic metal complex compound containing at least one metal selected from the group consisting of iridium (Ir), ruthenium (Ru), palladium (Pd), platinum (Pt), osmium (Os), and rhenium (Re). The ligand is preferably a nitrogen-containing aromatic heterocycle having a phenylpyridine skeleton, a phenylquinoline skeleton, or a carbene skeleton. However, it is not limited to these, and an appropriate complex can be selected according to the required luminescent color, device performance, and relationship with the host compound. Specifically, there can be mentioned a tris(2-phenylpyridyl)iridium complex, a tris{2-(2-thienyl)pyridyl}iridium complex, a tris{2-(2-benzothienyl)pyridyl}iridium complex, a tris(2-phenylbenzothiazole)iridium complex, a tris(2-phenylbenzooxazole)iridium complex, a tribenzoquinolineiridium complex, a bis(2-phenylpyridyl)(acetylacetonate)iridium complex, a bis{2-(2-thienyl)pyridyl}iridium complex, a bis{2-(2-benzothienyl)pyridyl}(acetylacetonate)iridium complex, and a bis(2-phenylbenzothiazole)(acetylacetonate)iridium complex. Iridium complex, bis(2-phenylbenzoxazole)(acetylacetone)iridium complex, bisbenzoquinoline(acetylacetone)iridium complex, bis{2-(2,4-difluorophenyl)pyridyl}(acetylacetone)iridium complex, tetraethylporphyrin platinum complex, {tris(thenoyltrifluoroacetone)mono(1,10-phenanthroline)}europium complex, {tris(thenoyltrifluoroacetone)mono(4,7-diphenyl-1,10-phenanthroline)}europium complex, {tris(1,3-diphenyl-1,3-propanedione)mono(1,10-phenanthroline)}europium complex, triacetylacetonate terbium complex, etc. In addition, the phosphorescent dopant described in Japanese Patent Laid-Open No. 2009-130141 can also be preferably used. Preferably, an iridium complex or a platinum complex can further improve the luminous efficiency.
[0096] The triplet light-emitting material used as the dopant material may be contained in the light-emitting layer in one type only, or two or more types may be mixed and used. When two or more triplet light-emitting materials are used, the total weight of the dopant materials is preferably 30% by weight or less, and more preferably 20% by weight or less, relative to the host material.
[0097] Preferred hosts and dopants in the triplet light-emitting system are not particularly limited, and specific examples include the following.
[0098] [Chemistry 15]
[0099]
[0100] [Chemistry 16]
[0101]
[0102] In the light-emitting element according to the embodiment of the present invention, it is also preferred that the light-emitting layer contain a triplet light-emitting material.
[0103] In addition, the light-emitting layer also preferably contains a thermally activated delayed fluorescent material. Thermally activated delayed fluorescence is explained in "The Most Advanced Organic Electroluminescence (Electroluminescence, EL)" (edited by Chiba Ya Andachi and Hiroshi Fujimoto, published by CMC) from page 87 to page 103. In the document, it is explained that by making the energy level of the excited singlet state and the excited triplet state of the fluorescent material close, the reverse energy migration from the excited triplet state with a low migration probability to the excited singlet state is usually efficiently generated, showing thermally activated delayed fluorescence (Thermally Activated delayedFluorescence, TADF). Furthermore, Figure 5 in the document illustrates the mechanism of delayed fluorescence. The luminescence of delayed fluorescence can be confirmed by transition photoluminescence (Photo Luminescence, PL) measurement.
[0104] Thermally activated delayed fluorescence materials are also generally referred to as TADF materials. Thermally activated delayed fluorescence materials can be materials that exhibit thermally activated delayed fluorescence through a single material, or materials that exhibit thermally activated delayed fluorescence through a variety of materials. In the case of comprising a variety of materials, it can be used as a mixture, or layers comprising each material can be stacked and used. As thermally activated delayed fluorescence materials, known materials can be used. For example, benzonitrile derivatives, triazine derivatives, disulfoxide derivatives, carbazole derivatives, indole and carbazole derivatives, dihydromorphazine derivatives, thiazole derivatives, oxadiazole derivatives, etc., but are not limited to these.
[0105] The element containing the TADF material in the light-emitting layer preferably further contains a fluorescent dopant in the light-emitting layer. This is because by using the TADF material, triplet excitons are converted into singlet excitons, and the fluorescent dopant accepts the singlet excitons, thereby achieving higher luminous efficiency or longer element life.
[0106] (Electron Transport Layer)
[0107] In the present invention, the electron transport layer refers to a layer that injects electrons from the cathode and then transports electrons. For the electron transport layer, it is expected that the electron injection efficiency is high and the injected electrons are efficiently transported. Therefore, the material constituting the electron transport layer is preferably a substance with large electron affinity, large electron mobility, excellent stability, and impurities that are not easy to produce as traps during manufacture and use. In particular, in the case of stacking with a thick film thickness, low molecular weight compounds are easy to crystallize and deteriorate the film quality, so it is preferred to maintain a stable film quality. The molecular weight is 400 or more. Compound. However, considering the transmission balance of holes and electrons, as long as the electron transport layer mainly plays a role in efficiently blocking the situation where the holes from the anode do not recombine and flow to the cathode side, even if it contains a material with not too high electron transport ability, the effect of improving the luminous efficiency is the same as that of the material containing high electron transport ability. Therefore, in the electron transport layer of the present invention, a hole blocking layer that can efficiently block the migration of holes is also included as a person with the same meaning, and the hole blocking layer and the electron transport layer can be constituted separately, or a plurality of materials can be stacked.
[0108] As the electron transport material used in the electron transport layer, for example, there can be listed condensed polycyclic aromatic derivatives of naphthalene, anthracene, etc., styryl aromatic ring derivatives such as 4,4'-bis(diphenylvinyl)biphenyl, quinone derivatives such as anthraquinone or diphenoquinone, phosphorus oxide derivatives, tris(8-hydroxyquinoline)aluminum (III) and other hydroxyquinoline complexes, benzohydroxyquinoline complexes, hydroxyazole complexes, methine azo (azomethine) complexes, tropolone metal complexes and flavonol metal complexes and other various metal complexes. In terms of further reducing the driving voltage and obtaining more efficient light emission, it is preferred to use the following compound: containing an element selected from carbon, hydrogen, nitrogen, oxygen, silicon, and phosphorus, and having a heteroaryl ring structure containing electron-accepting nitrogen.
[0109] The electron accepting nitrogen described herein refers to a nitrogen atom that forms multiple bonds with adjacent atoms. Because the nitrogen atom has a high electronegativity, the multiple bonds have the property of electron acceptance. Therefore, the aromatic heterocycle containing electron accepting nitrogen has a high electron affinity. The electron transport material with electron accepting nitrogen easily accepts electrons from the cathode with high electron affinity and can be driven with a lower voltage. In addition, the electrons supplied to the light-emitting layer become more, and the recombination probability becomes higher, so the luminous efficiency is further improved.
[0110] Examples of the heteroaryl ring containing electron-accepting nitrogen include a triazine ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a quinoline ring, a quinoxaline ring, a quinazoline ring, a naphthyridine ring, a pyrimidopyrimidine ring, a benzoquinoline ring, a phenanthroline ring, an imidazole ring, an oxazole ring, an oxadiazole ring, a triazole ring, a thiazole ring, a thiadiazole ring, a benzoxazole ring, a benzothiazole ring, a benzimidazole ring, and a phenanthroimidazole ring.
[0111] Examples of compounds having such heteroaryl ring structures include pyridine derivatives, triazine derivatives, quinazoline derivatives, pyrimidine derivatives, benzimidazole derivatives, benzoxazole derivatives, benzothiazole derivatives, oxadiazole derivatives, thiadiazole derivatives, triazole derivatives, pyrazine derivatives, phenanthroline derivatives, quinoline derivatives, benzoquinoline derivatives, oligopyridine derivatives such as bipyridine or terpyridine, quinoxaline derivatives, and naphthyridine derivatives. Among them, from the viewpoint of electron transport ability, imidazole derivatives such as tris(N-phenylbenzimidazol-2-yl)benzene, oxadiazole derivatives such as 1,3-bis[(4-tert-butylphenyl)1,3,4-oxadiazolyl]phenylene, triazole derivatives such as N-naphthyl-2,5-diphenyl-1,3,4-triazole, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (bathocuproin) or 1,3-bis(1,10-phenanthroline-9-yl)benzene can be preferably used. )benzene and other phenanthroline derivatives, 2,2'-bis(benzo[h]quinolin-2-yl)-9,9'-spirobifluorene and other benzoquinoline derivatives, 2,5-bis(6'-(2',2"-bipyridyl))-1,1-dimethyl-3,4-diphenylsilane and other bipyridine derivatives, 1,3-bis(4'-(2,2':6'2"-terpyridyl))benzene and other terpyridine derivatives, bis(1-naphthyl)-4-(1,8-naphthyridin-2-yl)phenylphosphine oxide and other naphthyridine derivatives.
[0112] In addition, if these derivatives have a condensed polycyclic aromatic skeleton, the glass transition temperature is increased, and the electron mobility is also increased, and the driving voltage of the light-emitting element can be further reduced, so it is preferred. Furthermore, if the durable life of the element is further improved, the ease of synthesis, and the easy acquisition of raw materials are considered, the condensed polycyclic aromatic skeleton is more preferably a fluoranthene skeleton, anthracene skeleton, pyrene skeleton or phenanthroline skeleton.
[0113] Preferred electron transport materials are not particularly limited, but specific examples include the following.
[0114] [Chemistry 17]
[0115]
[0116] In addition, the compound represented by the general formula (1) also has a high electron transport property and exhibits excellent properties as an electron transport material, and therefore is preferred.
[0117] The electron transport material may be used alone, or two or more of the electron transport materials may be mixed and used, or one or more of other electron transport materials may be mixed in the electron transport material and used. In addition, a donor compound may also be contained. Here, the so-called donor compound refers to a compound that facilitates the injection of electrons from the cathode or electron injection layer to the electron transport layer by improving the electron injection barrier, thereby improving the conductivity of the electron transport layer.
[0118] Preferred examples of donor compounds include alkali metals, inorganic salts containing alkali metals, complexes of alkali metals and organic substances, alkaline earth metals, inorganic salts containing alkaline earth metals, or complexes of alkaline earth metals and organic substances. Preferred types of alkali metals and alkaline earth metals include alkali metals such as lithium, sodium, potassium, rubidium, and cesium, which have low work functions and have a large effect of improving electron transport capabilities, and alkaline earth metals such as magnesium, calcium, cerium, and barium.
[0119] In addition, in terms of easy evaporation in vacuum and excellent operation, compared with metal monomers, it is preferably in the state of an inorganic salt or a complex with an organic substance. Furthermore, in terms of making the operation in the atmosphere easy and being able to easily adjust the added concentration, it is more preferably in the state of a complex with an organic substance. As examples of inorganic salts, there are: oxides such as LiO and Li2O, nitrides, fluorides such as LiF, NaF, KF, carbonates such as Li2CO3, Na2CO3, K2CO3, Rb2CO3, and Cs2CO3. In addition, as a preferred example of an alkali metal or alkaline earth metal, lithium and cesium can be cited from the perspective of further reducing the driving voltage. In addition, as a preferred example of an organic substance in a complex with an organic substance, there are: hydroxyquinoline, benzohydroxyquinoline, pyridylphenol, flavonol, hydroxyimidazopyridine, hydroxybenzoxazole, hydroxytriazole, etc. Among them, from the perspective of further reducing the driving voltage of the light-emitting element, a complex of an alkali metal and an organic substance is preferred. Furthermore, from the viewpoint of ease of synthesis and thermal stability, a complex of lithium and an organic substance is more preferred, and lithium quinolate (Liq) which is available at a relatively low cost is particularly preferred.
[0120] The ionization potential of the electron transport layer is not particularly limited, but is preferably 5.6 eV to 8.0 eV, and more preferably 5.6 eV to 7.0 eV.
[0121] The method for forming the above-mentioned layers constituting the light-emitting element is not particularly limited to resistance heating evaporation, electron beam evaporation, sputtering, molecular lamination, coating, etc., but resistance heating evaporation or electron beam evaporation is generally preferred in terms of element characteristics.
[0122] (Electron Injection Layer)
[0123] In the present invention, an electron injection layer may be provided between the cathode and the electron transport layer. The electron injection layer is generally inserted for the purpose of assisting the injection of electrons from the cathode to the electron transport layer. When inserted, a compound having a heteroaryl ring structure containing electron-accepting nitrogen may be used, and the donor material may also be used.
[0124] In addition, an insulator or a semiconductor inorganic substance may be used for the electron injection layer. The use of these materials is preferred because it can suppress short circuits of the light-emitting element and improve electron injection properties.
[0125] As such an insulator, it is preferable to use at least one metal compound selected from the group consisting of alkali metal chalcogenides, alkaline earth metal chalcogenides, alkali metal halides, and alkaline earth metal halides.
[0126] Specifically, preferred alkali metal chalcogenides include, for example, Li2O, Na2S, and Na2Se. Preferred alkaline earth metal chalcogenides include, for example, CaO, BaO, SrO, BeO, BaS, and CaSe. Preferred alkali metal halides include, for example, LiF, NaF, KF, LiCl, KCl, and NaCl. Preferred alkaline earth metal halides include, for example, fluorides such as CaF2, BaF2, SrF2, MgF2, and BeF2, or halides other than fluorides.
[0127] Furthermore, it is also possible to preferably use a complex of an organic substance and a metal. When a complex of an organic substance and a metal is used in the electron injection layer, it is easy to adjust the film thickness, so it is preferred. As a preferred example of the organic substance in such an organic metal complex, it is possible to list: hydroxyquinoline, benzohydroxyquinoline, pyridylphenol, flavonol, hydroxyimidazopyridine, hydroxybenzoxazole, hydroxytriazole, etc.
[0128] In addition, the compound represented by the general formula (1) also has a high electron injecting property and exhibits excellent properties as a material for the electron injecting layer, and therefore is preferred.
[0129] (Charge Generation Layer)
[0130] The charge generation layer in the present invention generally includes two layers, specifically, it can be used as a pn junction charge generation layer including an n-type charge generation layer and a p-type charge generation layer. The pn junction type charge generation layer generates charges by applying a voltage in the light-emitting element, or separates the charges into holes and electrons, and injects these holes and electrons into the light-emitting layer via a hole transport layer and an electron transport layer. Specifically, in a light-emitting element stacked with light-emitting layers, the charge generation layer as an intermediate layer functions. The n-type charge generation layer supplies electrons to the first light-emitting layer present on the anode side, and the p-type charge generation layer supplies holes to the second light-emitting layer present on the cathode side. Therefore, the luminous efficiency of the light-emitting element stacked with multiple light-emitting layers can be further improved and the driving voltage can be reduced, and the durable life of the element can also be further improved.
[0131] The n-type charge generation layer comprises an n-type dopant and a host, which can use existing materials. For example, as the n-type dopant, an alkali metal, an alkaline earth metal or a rare earth metal can be used. In addition, as the host, a triazine derivative, a phenanthroline derivative or an oligopyridine derivative can be used. In particular, the compound represented by the general formula (1) and the phenanthroline derivative show excellent properties as the host of the n-type charge generation layer, and are therefore preferred.
[0132] When a phenanthroline derivative is used as the main component of the n-type charge generating layer, it is preferable to use a compound represented by the general formula (1) as the electron transport material because the electron injection barrier between these materials is small, thereby further reducing the driving voltage of the device.
[0133] The p-type charge generation layer includes a p-type dopant and a host, which can use existing materials. For example, as a p-type dopant, tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ), tetracyanoquinodimethane derivatives, radialene derivatives, iodine, FeCl3, FeF3 and SbCl5 can be used. As a p-type dopant, a radialene derivative is preferred. As a host, an arylamine derivative is preferred.
[0134] The thickness of the organic layer depends on the resistance value of the light-emitting material and cannot be limited, but is preferably 1 nm to 1000 nm. The thickness of the light-emitting layer, electron transport layer, and hole transport layer is preferably 1 nm to 200 nm, more preferably 5 nm to 100 nm.
[0135] The light-emitting element of the embodiment of the present invention has the function of converting electrical energy into light. Here, direct current is mainly used as electrical energy, but pulse current or alternating current can also be used. There is no particular limitation on the current value and voltage value. If the power consumption or life of the element is taken into consideration, it is preferably selected in a manner to obtain the maximum brightness with the lowest possible energy.
[0136] The light-emitting element according to the embodiment of the present invention can be preferably used as a display device such as a display that displays in a matrix and / or segment manner, for example.
[0137] The light-emitting element of the embodiment of the present invention can also be preferably used as a backlight for various devices. Backlight is mainly used for the purpose of improving the visibility of display devices such as displays that do not emit light by themselves, and can be used in liquid crystal displays, clocks, audio devices, car panels, display boards, and signs. In particular, the light-emitting element of the present invention can be preferably used in the backlight of personal computers for which thinning is being studied in liquid crystal displays, and can provide a thinner and lighter backlight than the existing ones.
[0138] The light-emitting element of the embodiment of the present invention can also be preferably used as various lighting devices. The light-emitting element of the embodiment of the present invention can make high luminous efficiency and high color purity coexist, and further, can realize thinning and light weight, so that a lighting device with low power consumption, bright luminous color and high design can be realized.
[0139] Example
[0140] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not limited to these Examples.
[0141] Synthesis Example 1: Synthesis of Compound 1
[0142] [Chemistry 18]
[0143]
[0144] A mixed solution of 2.7 g of 4'-(4-bromophenyl)-2,2':6'2"-terpyridine, 1.6 g of 4-(1-pyrene)phenylboronic acid, 50 mg of dichlorobis(triphenylphosphine palladium) dichloride, 6 ml of 1.5M sodium carbonate aqueous solution and 70 ml of dimethoxyethane was heated and stirred under reflux for 5 hours under a nitrogen flow. After cooling to room temperature, water was added and filtered, washed with methanol, and vacuum dried. The obtained solid was refined by silica gel column chromatography, the solvent was evaporated and removed, and the obtained solid was vacuum dried to obtain 2.3 g of compound 1.
[0145] The obtained compound 1 was heated at 1×10 -3 The compound 1 was used in the examples after being purified by sublimation at about 340° C. under a pressure of 1.3 Pa. The purity (area % at a measurement wavelength of 254 nm) of the compound 1 before and after the sublimation purification was 99.9%.
[0146] After sublimation purification, the product was analyzed by mass spectrometry (MS). 1 H-NMR (Nuclear Magnetic Resonance) analysis identified the structure of compound 1. The analysis results are shown below.
[0147] MS (m / z): 586 [M+H] +
[0148] 1 H-NMR (400MHz, CDCl3) δ: 8.833 (s, 2H), 8.755 (d, J = 2.4Hz, 2H), 8.770 (d, J = 7.6Hz, 2H), 8.263 (dd, J = 6.4, 8.8Hz, 2H), 8.198 (dd, J=8.8, 9.2Hz, 2H), 8.000-8.114 (m, 7H), 7.875-7.950 (m, 6H), 7.760 (d, J=8.4Hz, 2H), 7.358-7.385 (m, 2H).
[0149] Synthesis Example 2: Synthesis of Compound 2
[0150] [Chemistry 19]
[0151]
[0152] A mixed solution of 4.0 g of 4'-(4-bromophenyl)-2,2':6'2"-terpyridine, 1.7 g of 3-chlorophenylboronic acid, 72 mg of dichlorobis(triphenylphosphine palladium) dichloride, 10 ml of 1.5M sodium carbonate aqueous solution and 70 ml of dimethoxyethane was heated and stirred under reflux for 3 hours under a nitrogen flow. After cooling to room temperature, water was added and filtered, washed with methanol, and vacuum dried to obtain 4.0 g of intermediate A.
[0153] Secondly, a mixed solution of 2.9 g of intermediate A, 1.8 g of 1-pyreneboric acid, 50 mg of dichlorobis(triphenylphosphine palladium) dichloride, 6 ml of 1.5 M potassium phosphate tripotassium aqueous solution and 40 ml of 1,4-dioxane was heated and stirred for 7 hours under a nitrogen stream and reflux. After cooling to room temperature, water was added and filtered, washed with methanol, and vacuum dried. The obtained solid was refined by silica gel column chromatography, evaporated and the solvent was removed, and the obtained solid was vacuum dried to obtain 1.7 g of compound 2.
[0154] The obtained compound 2 was prepared by using an oil diffusion pump at 1×10 -3The compound 2 was used in the examples after being purified by sublimation at about 340° C. under a pressure of 1.27 Pa. The HPLC purity (area % at a measurement wavelength of 254 nm) of the compound 2 before and after the sublimation purification was 99.9%.
[0155] After sublimation purification, the product was analyzed by mass spectrometry (MS) and 1 H-NMR analysis identified the structure of Compound 2. The analysis results are shown below.
[0156] MS (m / z): 586 [M+H] +
[0157] 1 H-NMR (400MHz, CDCl3) δ: 8.670-8.797 (m, 6H), 8.150-8.262 (m, 4H), 8.095-8.150 (m, 2H ), 8.000-8.095(m, 5H), 7.765-7.995(m, 6H), 7.620-7.765(m, 2H), 7.320-7.380(m, 2H).
[0158] Next, the evaluation method in each example is described.
[0159] (Drive voltage)
[0160] The devices obtained in Examples 1 to 11 and Comparative Examples 1 to 14 were each charged at 10 mA / cm 2 The DC drive was performed and the initial drive voltage was measured. Furthermore, the current density was 10 mA / cm2 at a temperature of 70°C. 2 The voltage at the time of DC driving for 100 hours was used to calculate the voltage rise from the initial driving voltage.
[0161] In addition, the light-emitting elements obtained in Examples 12 to 22 and Comparative Examples 15 to 28 were each irradiated at a luminance of 1000 cd / m 2 The lamp was turned on and the initial driving voltage was measured. Furthermore, the current density at room temperature was measured at 10 mA / cm 2 The voltage when the constant current is driven for 100 hours is used to calculate the voltage rise from the initial driving voltage.
[0162] In addition, the light emitting devices obtained in Examples 23 to 44 and Comparative Examples 29 to 56 were each subjected to a 10 mA / cm 2 Driven by current density of , calculate the initial driving voltage.
[0163] The smaller the initial driving voltage is, the lower the voltage can be driven, so it can be evaluated that the luminous efficiency (brightness / power) is better. In addition, the smaller the voltage rise is, the better the durable life can be evaluated.
[0164] (External quantum efficiency)
[0165] The light emitting devices obtained in Examples 12 to 22 and Comparative Examples 15 to 28 were each subjected to a current density of 10 mA / cm 2 The lamp was turned on, and the external quantum efficiency was measured to evaluate the luminous efficiency. The higher the external quantum efficiency, the better the luminous efficiency.
[0166] (brightness)
[0167] The light emitting devices obtained in Examples 23 to 44 and Comparative Examples 29 to 56 were heated at 10 mA / cm 2 The lamp is turned on, the brightness is measured, and the luminous efficiency is evaluated. The higher the brightness, the better the luminous efficiency can be evaluated.
[0168] (Durable life)
[0169] The light emitting devices obtained in Examples 12 to 44 and Comparative Examples 15 to 56 were heated at 10 mA / cm 2 The device is driven continuously with a constant current and the time for the brightness to decrease by 20% from the initial brightness is measured as the durability life.
[0170] Example 1
[0171] A glass substrate (manufactured by Geomatec, 11Ω / Y, sputtered product) with a 125nm ITO transparent conductive film deposited as an anode was cut into 38mm×46mm and etched. The obtained substrate was ultrasonically cleaned for 15 minutes using "Semico clean" (registered trademark) 56 (trade name, manufactured by Furuchi Chemical Co., Ltd.), and then cleaned with ultrapure water. Immediately before the element was made, the substrate was treated with UV-ozone for 1 hour, placed in a vacuum evaporation device, and evacuated until the vacuum degree in the device reached 5×10 -4 Pa or less. By the resistance heating method, the compound 1 obtained by the synthesis example 1 and the metal element Li as a dopant were evaporated at a deposition rate ratio of compound 1: Li = 99: 1 for 100 nm, forming a layer with a weight ratio of 99: 1. After that, aluminum was evaporated for 60 nm as a cathode to make a 5 mm × 5 mm square element. The film thickness described here is the value displayed by the quartz oscillation film thickness monitor, which is also common to other embodiments and comparative examples.
[0172] The element was evaluated by the above method. As a result, the initial driving voltage was 0.030 V, and the voltage increase amount when driven at 70° C. for 100 hours was 0.001 V.
[0173] [Chemistry 20]
[0174]
[0175] Example 2 to Example 11, Comparative Example 1 to Comparative Example 14
[0176] A device was produced in the same manner as in Example 1 except that the compound used and the vapor deposition rate ratio of the compound to the metal element were changed as shown in Table 1. The results of each example and comparative example are shown in Table 1. Compounds 2 to 23 are the following compounds.
[0177] [Chemistry 21]
[0178]
[0179] [Chemistry 22]
[0180]
[0181] [Chemistry 23]
[0182]
[0183] [Table 1]
[0184]
[0185] Example 12
[0186] A glass substrate (manufactured by Geomatec, 11Ω / Y, sputtered product) with a 165nm ITO transparent conductive film deposited as an anode was cut into 38mm×46mm and etched. The obtained substrate was ultrasonically cleaned for 15 minutes using "Semico clean" 56 (trade name, manufactured by Furuchi Chemical Co., Ltd.), and then cleaned with ultrapure water. Immediately before the element was made, the substrate was treated with UV-ozone for 1 hour, placed in a vacuum evaporation device, and evacuated until the vacuum degree in the device reached 5×10 -4Pa or less. First, 5 nm of HAT-(CN)6 is evaporated by resistance heating as a hole injection layer, and then 50 nm of HT-1 is evaporated as a hole transport layer. Secondly, a mixed layer of the main material H-1 and the dopant material D-1 is evaporated to a thickness of 20 nm in a manner that the doping concentration becomes 5 weight % as a light-emitting layer. Next, ET-1 and 2E-1 are evaporated to a thickness of 35 nm in a manner that the evaporation rate ratio becomes ET-1:2E-1=1:1 as an electron transport layer. Next, compound 1 obtained by synthesis example 1 and the metal element Li as a dopant are evaporated to 10 nm in a manner that the evaporation rate ratio becomes compound 1:Li=99:1 as an electron injection layer. After that, 60 nm of aluminum is evaporated as a cathode to make a 5 mm×5 mm square light-emitting element.
[0187] The light-emitting element was evaluated by the method, and the initial driving voltage was 4.05 V, the external quantum efficiency (luminous efficiency) was 5.77%, the durable life was 1000 hours, and the voltage rise when driven for 100 hours at room temperature was 0.001 V. In addition, HAT-(CN)6, HT-1, H-1, D-1, ET-1 and 2E-1 are the compounds shown below.
[0188] [Chemistry 24]
[0189]
[0190] Examples 13 to 22, Comparative Examples 15 to 28
[0191] A light-emitting element was produced in the same manner as in Example 12, except that the compound used and the vapor deposition rate ratio of the compound to the metal element were changed as shown in Table 2. Table 2 shows the results of each of the Examples and Comparative Examples.
[0192] [Table 2]
[0193]
[0194] Embodiment 23
[0195] A glass substrate (manufactured by Geomatec, 11Ω / Y, sputtered product) with a 165nm ITO transparent conductive film deposited as an anode was cut into 38mm×46mm and etched. The obtained substrate was ultrasonically cleaned for 15 minutes using "Semico clean" 56 (trade name, manufactured by Furuchi Chemical Co., Ltd.), and then cleaned with ultrapure water. Immediately before the element was made, the substrate was treated with UV-ozone for 1 hour, placed in a vacuum evaporation device, and evacuated until the vacuum degree in the device reached 5×10 -4Pa or less. First, 5 nm of HAT-(CN)6 was deposited as a hole injection layer by resistance heating. Then, a light-emitting unit (first light-emitting unit) including a hole transport layer, a light-emitting layer, and an electron transport layer was formed on the hole injection layer.
[0196] Specifically, 50nm of HT-1 is evaporated as a hole transport layer, and then a mixed layer of the main material H-1 and the dopant material D-1 is evaporated to a thickness of 20nm in a manner that the doping concentration becomes 5 weight% as a light-emitting layer. Then, ET-1 and 2E-1 are evaporated to a thickness of 35nm in a manner that the evaporation speed ratio becomes ET-1:2E-1=1:1 as an electron transport layer.
[0197] On the first light-emitting unit, compound 1 obtained by synthesis example 1 and metal element Li as a dopant are evaporated at a deposition rate ratio of compound 1:Li=99:1 to form an n-type charge generation layer, and then HAT-(CN)6 is evaporated to form a p-type charge generation layer at a thickness of 10 nm.
[0198] After the charge generation layer, the second light-emitting unit was formed in the same manner as the first light-emitting unit. Then, the compound 1 obtained in Synthesis Example 1 and the metal element Li as a dopant were evaporated at a deposition rate ratio of compound 1:Li = 99:1 to form an electron injection layer, and then aluminum was evaporated to form a cathode to form a 5 mm × 5 mm square light-emitting element.
[0199] The light-emitting element was evaluated by the method, and the initial driving voltage was 8.22 V and the brightness was 1820 cd / m 2 , durable life is 2500 hours.
[0200] Examples 24 to 33, Comparative Examples 29 to 42
[0201] A light-emitting element was produced in the same manner as in Example 23, except that the compound used and the vapor deposition rate ratio of the compound to the metal element were changed as shown in Table 3. Table 3 shows the results of each of the Examples and Comparative Examples.
[0202] [Table 3]
[0203]
[0204] Embodiment 34
[0205] A light-emitting element was prepared in the same manner as in Example 23, except that Compound 1 obtained in Synthesis Example 1 was used instead of ET-1 in forming the electron transport layer, and ET-2 was used instead of Compound 1 in forming the n-type charge generation layer.
[0206] The light emitting element was evaluated by the method, and the initial driving voltage was 8.10 V and the brightness was 1800 cd / m 2 , the durable life is 2450 hours. ET-2 is the compound shown below.
[0207] [Chemistry 25]
[0208]
[0209] Examples 35 to 44, Comparative Examples 43 to 56
[0210] A light-emitting element was produced in the same manner as in Example 34, except that the compound used and the vapor deposition rate ratio of the compound to the metal element were changed as shown in Table 4. Table 4 shows the results of each of the Examples and Comparative Examples.
[0211] [Table 4]
[0212]
Claims
1. A compound represented by the following general formula (1); In the general formula (1), X 3 is a nitrogen atom, X 1 , X 2 L is methine; 1 is a substituted or unsubstituted biphenylene, terphenylene, naphthylene, quaterphenylene, dimethylfluorenylene, diphenylfluorenylene or spirobifluorenylene; wherein, When these groups are substituted, the substituent is an alkyl group or an alkoxy group; A is a pyrenyl group.
2. The compound according to claim 1, wherein in the general formula (1), L 1 It is biphenylene, terphenylene or naphthylene.
3. The compound according to claim 1 or 2, wherein in the general formula (1), L 1 It is a biphenylene group.
4. An organic thin film light emitting device, which is a light emitting device having at least an electron transport layer and a light emitting layer between an anode and a cathode and emits light by electric energy, wherein the electron transport layer contains the compound according to any one of claims 1 to 3. 5 . The organic thin film light-emitting element according to claim 4 , wherein the electron transport layer further contains an alkali metal complex compound. 6 . The organic thin film light-emitting element according to claim 4 , wherein a charge generation layer is further present between the anode and the cathode, and the charge generation layer contains a compound having a phenanthroline skeleton.
7. An organic thin film light emitting device, which is a light emitting device having at least a charge generation layer and a light emitting layer between an anode and a cathode and emits light by electric energy, wherein the charge generation layer contains the compound according to any one of claims 1 to 3. 8 . The organic thin film light-emitting element according to claim 7 , wherein the charge generation layer further contains alkali metal atoms. 9 . The organic thin film light emitting element according to claim 8 , wherein the alkali metal atom is Li.
10. An organic thin film light emitting device, which comprises at least an electron injection layer and a light emitting layer between an anode and a cathode and emits light by electric energy, wherein the electron injection layer contains the compound according to any one of claims 1 to 3.
11. A display device comprising the organic thin film light emitting element according to any one of claims 4 to 10.
12. A lighting device comprising the organic thin film light emitting element according to any one of claims 4 to 10.
Citation Information
Patent Citations
Organic el device and solution containing organic el material
JP2009130141A
Novel heterocyclic compounds and organic light-emitting devices utilizing them
JP2018532688A
Light emitting element material and light emitting element
WO2012173073A1
Fluoranthene derivative, electronic device containing same, light-emitting element, and photoelectric conversion element
WO2015182547A1
Antenna controlling device and controlling method based on wireless access in vehicular environment
WO2016060322A1